The Microbiome – The Unscheduled Parameter for Future Therapies - Beule, Achim G. (Laryngo-Rhino-Otologie, 2018)
The microbiome is defined as the total of cellular microorganisms of baczerial, viral or e. g., parasite origin living on the surface of a body. Within the anatomical areas of otorhinolaryngology, a significant divergence and variance can be demonstrated. For ear, nose, throat, larynx and cutis different interactions of microbiome and common factors like age, diet and live style factors (e. g., smoking) have been detected in recent years. Besides, new insights hint at a passible pathognomic role of the microbiome towards diseases in the ENT area. This review article resumes the present findings of this rapidly devloping scientific area.
Keywords: Microbiome; sinusitis; head and neck cancer; otitis